A Four-Wheel-Rhombus-Arranged Mobility System for a New Lunar Robotic Rover. (28th October 2013) - Wen, Guilin; Ma, Chuanshuai; Cheng, Dong; Jin, Qiutan; Chen, Zhewu; Yang, Xingfa; Yin, Hanfeng; Zhou, Jingyu
Different from traditional ground vehicles, planetary robotic rovers with limited weight and power need to travel in unfamiliar and extremely arduous environments. In this paper, a newly developed four-wheel-rhombus-arranged (FWRA) mobility system is presented as a lunar robotic rover with high mobility and a low-weight structure. The mobility system integrates independent active suspensions with a passive rotary link structure. The active suspension with swing arms improves the rover's capacity to escape from a trapped environment whereas the passive rotary link structure guarantees continuous contact between the four wheels and the terrain. The four-wheel-three-axis rhombus configuration of the mobility system gives a high degree of lightweight structure because it has a simple mechanism with the minimum number of wheels among wheeled rovers with three-axis off-road mobility. The performance evaluation of the lightweight nature of the structure, manoeuvrability and the mobility required in a planetary exploring environment are illustrated by theoretical analysis and partly shown by experiments on the developed rover prototype.